2021
DOI: 10.3390/pathogens10070789
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Treatment Outcome with Inflammatory Biomarkers after 2 Months of Therapy in Pulmonary Tuberculosis Patients: Preliminary Results

Abstract: Pro-inflammatory mediators play an important role in the pathogenesis of pulmonary tuberculosis. Consecutively, 26 pulmonary tuberculosis patients were enrolled in our study based on the exclusion criteria. We have used Spearman’s correlation analysis, hierarchical clustering and regression modelling to evaluate the association of 11 biomarkers with culture status after antituberculosis treatment. The results of our study demonstrated that six inflammatory biomarkers of 11, C-reactive protein (CRP), white bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Given this, these three markers could be useful for monitoring subjects with APTB during standard TB treatment. Our findings align with previous studies, which emphasize the significance of monitoring circulating acute phase reactants and cytokines as parameters that aid in distinguishing individuals with TB both before and after standard TB treatment [ 22 , 62 , 86 , 87 ]. Thus, the importance of the study lies in the fact that systemic inflammation can be evaluated with the determination of these inflammatory mediators (IFN-γ, CRP, and total sialic acid), and this evaluation could be useful in conjunction with sputum smear microscopy to evaluate the response to anti-tuberculosis treatment in subjects with APTB and TBDM [ 7 , 17 , 29 , 82 ].…”
Section: Discussionsupporting
confidence: 91%
“…Given this, these three markers could be useful for monitoring subjects with APTB during standard TB treatment. Our findings align with previous studies, which emphasize the significance of monitoring circulating acute phase reactants and cytokines as parameters that aid in distinguishing individuals with TB both before and after standard TB treatment [ 22 , 62 , 86 , 87 ]. Thus, the importance of the study lies in the fact that systemic inflammation can be evaluated with the determination of these inflammatory mediators (IFN-γ, CRP, and total sialic acid), and this evaluation could be useful in conjunction with sputum smear microscopy to evaluate the response to anti-tuberculosis treatment in subjects with APTB and TBDM [ 7 , 17 , 29 , 82 ].…”
Section: Discussionsupporting
confidence: 91%
“…and the host, based on the interaction of bacterial strains and inflammatory biomarkers released by macrophages, monocytes, neutrophils, and lymphocytes ( 30 34 ). C-reactive protein (CRP) is also a non-specific biomarker in TB, with highly increased plasmatic concentrations, due to sputum bacillary load and severity of inflammation ( 30 , 35 ). Human liver CRP production usually forgoes clinical symptoms ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al established clinical indicators in routine blood tests to distinguish between active TB and latent tuberculosis infection (LTBI) [ 24 ]. Stefanescu et al supposed that inflammatory biomarkers, including CRP, WBC, neutrophils, interferon-gamma inducible protein 10, CRP to albumin ratio (CAR), neutrophil to albumin ratio (NAR) and serum LL37, had a good prediction ability for 2-months treatment outcomes of pulmonary TB patients [ 25 ]. Previous studies also suggested that the power of a single index to predict prognosis was limited, and the combination of clinical indicators can effectively improve the prediction effectiveness.…”
Section: Discussionmentioning
confidence: 99%